Burden of Proof under the Saudi Companies Law - Abdulrahman Mohammed Abdulaziz Al-Humaid (International Journal of Law Research and Studies, 2026)
This study examines the burden of proof under the Saudi Companies Law and how the legislator allocates it in certain corporate disputes. The introductory section defines the burden of proof and highlights the particular nature of corporate disputes. The study addresses three main instances. First, concerning the civil liability of auditors under Article (20/7), where multiple auditors are jointly liable, the burden shifts to the auditor to prove non-participation in the fault giving rise to liability. Second, under Article (31), in claims alleging that a director or board member failed to perform their duties or act in good faith regarding decisions taken or voted upon, the burden of proof rests on the claimant alleging the breach. Third, under Articles (28) and (71), the burden lies on directors or dissenting members to prove their objection to unlawful resolutions, as well as on absent members to establish lack of knowledge of the decision or inability to object upon becoming aware of it. The study concludes that the Saudi regulator adopts a flexible approach, distributing the burden of proof according to the parties’ positions and the nature of each dispute.